2022
DOI: 10.3389/fcvm.2022.834967
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 21 Predicts Short-Term Prognosis in Patients With Acute Heart Failure: A Prospective Cohort Study

Abstract: BackgroundRecent studies of fibroblast growth factor 21 (FGF21), first recognized as a regulator of glucose and lipid metabolism, have found that the level of in serum FGF21 is associated with the prognosis of many cardiovascular diseases, but its relationship to acute heart failure (AHF) patients remains unknown. Our study aimed to investigate whether circulating FGF21 could predict the short-term prognosis of AHF patients.MethodsFour hundred and two AHF patients and 19 healthy controls were recruited into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The nine included studies contained five cohort (19-23) and four case-control studies (24)(25)(26)(27). Seven studies reported the effect sizes of patients with CAD (19)(20)(21)(22)(23)(24)(25), and three studies specifically focused on patients with HF (23,26,27). A total of 2674 patients from four studies were included in the analysis of the primary endpoint MACE for CAD (20,22,24,25).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The nine included studies contained five cohort (19-23) and four case-control studies (24)(25)(26)(27). Seven studies reported the effect sizes of patients with CAD (19)(20)(21)(22)(23)(24)(25), and three studies specifically focused on patients with HF (23,26,27). A total of 2674 patients from four studies were included in the analysis of the primary endpoint MACE for CAD (20,22,24,25).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2674 patients from four studies were included in the analysis of the primary endpoint MACE for CAD (20,22,24,25). A total of 771 patients with HF from three studies were included in the analysis of a composite endpoint of death or readmission for HF (23,26,27). Details of the studies included in this meta-analysis are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations